Environmental Pollutants, Climate Change, and Its Far-reaching Impacts on Sexual and Reproductive Health - Adarsh Tripathi; T. S. Sathyanarayana Rao (Journal of Psychosexual Health)
Evidence suggests that environmental pollutants may negatively impact the reproductive health of both men and women. The aim of the current editorial is to explore the complex and multifaceted impact of climate change on the sexual and reproductive health of individuals in order to spread awareness and create a discourse about the issue that ultimately leads to some policy and systematic changes that help the people in need of it. Environmental pollutants including heavy metals, fine particulate matter, and electromagnetic radiation are endocrine disruptors that significantly impact reproductive health of both males and females. Moreover, socioenvironmental factors such as food insecurity and financial instability may also exacerbate sexual health concerns by increasing risky behaviors and limited access to contraceptives or healthcare services.